Optimization of Churning Resistance of Hypoid Gear for Automobile Rear Axle - Yunxiao Shen; Jinli Xu; Jiwei Zhu; Wenchao Yang (Jixie chuandong)
The purpose of is to discuss an accessible approach to reduce the churning resistance of hypoid gear of automobile rear axle. A CFD model of automobile rear axle is conducted based on VOF and standard k-ε model， the churning power loss mechanism of rear axle hypoid gear is analyzed. The method of removing the bolt structure and adding baffle plates on both sides of hypoid gear is proposed to reduce the churning resistance. Through Fluent simulation， the churning resistance before and after improvement rear axle hypoid gear is analyzed， and compared with the empirical formula， and verified by experiments. The results show that， results of simulation analysis and test are in good agreement， the empirical formula is in good agreement with the simulation result， but less than the experimental value， the proper structural improvement and addition of oil baffle can significantly reduce the rear axle churning resistance， as the speed increases， the resistance reduction value increases， the maximum drag reduction can reach 35.9%.